Radiation protection in mammography for breast cancer screening: not covered by the French press. (June 2020) - Britel, M.; Bourguignon, M.; Preau, M.
Abstract: Background: In the context of major exposure to medical-based ionizing radiation (IR), French health institutions agree that adopting a precautionary approach is essential. A number of scientific studies have highlighted the risk of developing breast cancer after exposure to IR, even from low doses. However, the information circulating on the subject is varied. Objectives: A study of the mainstream press was performed to better understand the elements constituting women's representations of IR in mammography for breast cancer screening. Study design: The data used came from a corpus created with the mainstream press database 'Europresse.' The keyword 'mammography' was chosen. The software package Iramuteq was used to perform a statistical analysis of textual data using the Reinert method. Results: This study highlights a paradox between the social principle of prevention and the discourse elements on mammography screening present in the mainstream press. Conclusion: The general French press does not take into account radiation protection in cancer screening discourses. A greater effort to provide information on this subject is needed. Highlights: Radiation protection in mammography is taken into account in national recommendations. The mainstream press does not address radiation protection in mammography. Mainstream press explains national breast cancer screening recommendations.